Production of Stoving paints and their testing - Unnati Vishnoi (Environment Conservation Journal, 2007)
Stoving  paint  is used  in refrigerators,  fans,  scooters  etc.  This  paint  doesn’t  break  because  of high  temperature. The  stoving  paint  is  prepared  by  the  ball  mill.  After  manufacturing,   this  paint  is  tested  for  flexibility  and adhesion,  hardness,  resistance  of  acid  and  alkali,  consistency  and  its  volatile  matter.